Optimization of Prosthodontic Computer‐Aided Designed Models: A Virtual Evaluation of Mesh Quality Reduction Using Open Source Software. Issue 5 (2nd December 2020) - Farook, Taseef Hasan; Barman, Aparna; Abdullah, Johari Yap; Jamayet, Nafij Bin
Abstract: Purpose: Mesh optimization reduces the texture quality of 3D models in order to reduce storage file size and computational load on a personal computer. This study aims to explore mesh optimization using open source (free) software in the context of prosthodontic application. Materials and Methods: An auricular prosthesis, a complete denture, and anterior and posterior crowns were constructed using conventional methods and laser scanned to create computerized 3D meshes. The meshes were optimized independently by four computer‐aided design software (Meshmixer, Meshlab, Blender, and SculptGL) to 100%, 90%, 75%, 50%, and 25% levels of original file size. Upon optimization, the following parameters were virtually evaluated and compared; mesh vertices, file size, mesh surface area (SA), mesh volume (V), interpoint discrepancies (geometric similarity based on virtual point overlapping), and spatial similarity (volumetric similarity based on shape overlapping). The influence of software and optimization on surface area and volume of each prosthesis was evaluated independently using multiple linear regression. Results: There were clear observable differences in vertices, file size, surface area, and volume. The choice of software significantly influenced the overall virtual parameters of auricular prosthesis [SA: F(4, 15) = 12.93, R 2 = 0.67, p < 0.001. V: F(4, 15) = 9.33, R 2 = 0.64, p < 0.001] and complete denture [SA: F(4, 15) = 10.81, R 2 = 0.67, p < 0.001. V: F(4, 15) = 3.50, R 2 = 0.34, p = 0.030] across optimization levels. Interpoint discrepancies were however limited to <0.1mm and volumetric similarity was >97%. Conclusion: Open‐source mesh optimization of smaller dental prostheses in this study produced minimal loss of geometric and volumetric details. SculptGL models were most influenced by the amount of optimization performed.